Top-Cited Articles in Rehabilitation - Shadgan, Babak; Roig, Marc; HajGhanbari, Bahareh; Reid, W. Darlene (Archives of physical medicine and rehabilitation, 2010)
Shadgan B, Roig M, HajGhanbari B, Reid WD. Top-cited articles in rehabilitation. To identify the 100 top-cited articles ever published in rehabilitation journals and to analyze their characteristics as a quantitative approach to investigating the quality and evolution of rehabilitation research. The Institute for Scientific Information Web of Knowledge Database and the 2007 and 2008 Journal Citation Report Science Editions were used to retrieve the 100 top-cited articles from 30 rehabilitation dedicated journals. The 100 top-cited articles included randomized controlled trials, case-control studies, case series studies, case reports, methodologic studies, systematic reviews, narrative reviews, and expert opinions. Two independent reviewers performed data extraction from the retrieved articles and compared their results. The Sackett's initial rules of evidence were used to categorize the type of study design as well as to evaluate the level of evidence provided by the results of the 100 top-cited articles. Among the 45,700 articles published in these journals, the 100 top-cited articles were published between 1959 and 2002 with an average of 200 citations an article (range, 131–1109). Top-cited articles were all English-language, primarily from North America (United States=67%; Canada=11%) and published in 11 journals led by the Archives of Physical Medicine and Rehabilitation. Eighty-four percent of the articles were original publications and were most commonly prospective (76%) case series studies (67%) that used human subjects (96%) providing level 4 evidence. Neurorehabilitation (41%), disability (19%), and biomechanics (18%) were the most common fields of study. We demonstrated that methodologic observational studies performed in North America and published in English have had the highest citations in rehabilitation journals.